Apparent Helix-Coil Transition for Poly(L-Alanine) as Measured by Nuclear Magnetic Resonance(*) - Goodman, Murray (National Academy of Sciences, 1973)
The previous contention by several groups that double peaks that arise in NMR spectra from NH and α-CH protons of poly L-alanines are caused by the coexistence of helical and random-coil structures in solution is disputed.